Integrating Counseling into the Elementary School Curriculum Implications for Building a Strong Educational Foundation - Chinwe Augustina Enwere; Adaobi Jennifer Iloakasia (Journal of Indonesian Primary School, 2025)
Many elementary school pupils face emotional, social, and behavioral challenges that can negatively affect their academic performance and overall development. Despite this, counseling services are often underutilized or absent in early education, leaving gaps in pupils’ social-emotional support. The study adopted a descriptive survey design and was conducted among teachers and professional counsellors in Anambra State. Data were collected electronically using Google Form from 85 respondents categorized by years of experience. A structured questionnaire measured counseling integration, its impact on pupils’ socio emotional development, and its educational implications. Data were analyzed using descriptive statistics and ANOVA at 0.05 significance level. Eighty-five respondents participated, with most having less than five years of experience (35.3%), followed by 15 to 25 years (30.6%). Findings showed strong agreement that counseling was integrated through structured activities, collaboration, timetable inclusion, and management support, though classroom integration of guidance topics was weaker. Integrated counseling positively influenced pupils’ emotional stability, relationships, and participation, though its effect on behavioral reduction was modest. Respondents also agreed that counseling strengthened discipline and overall school performance. ANOVA results revealed significant differences based on years of experience across all three hypotheses, leading to rejection of the null hypotheses. The study concludes that policymakers, educators, and school administrators must prioritize counseling integration to cultivate emotionally resilient, socially competent, and academically motivated pupils, thereby laying a firm foundation for lifelong learning.